Management of Stage-4 HIV with Cerebral Toxoplasmosis Coinfection and SIADH Complication - Laksono, Pandu; Oktavia, Erlin; Putri, Hidayati Adi; Herawati, Fauna (Faculty of Medicine, Universitas Padjadjaran, 2024)
HIV/AIDS stage 4 is the stage where the HIV/AIDS patients have low immunity protection against infections, which can led to coinfections and complications. This case report presented an evaluation of the diagnosis and treatment of an HIV/AIDS stage 4 patient with cerebral toxoplasmosis coinfection and SIADH complications. A man (47 years, 35 kg), married with two children, complaining of weakness, nausea, vomiting, weight loss, and low appetite. Sodium level were measured, showing a 117 mg/dL level that continued to decrease throughout the patient's treatment. Five days later, the patient lost his consciousness with a GCS score of 224, indicating severe brain injury, and was diagnosed with cerebral toxoplasmosis based on the result of head CT-SCAN with contrast. On day 6, the patient was tested positive for HIV and diagnosed with stage 4 with an absolute CD4 count of 4 cells/μl. Therapy was provided by giving pyrimethamine-clindamycin therapy for cerebral toxoplasmosis, followed by Tenofovir, Lamivudine, and Evafirenz as antiretroviral therapy. Treatment for hyponatremia was done by administration of 3% NaCl and tolvaptan. The patient started experiencing an improvement in consciousness after the 10th day of medication, and sodium levels fluctuated throughout the treatments. Patient was discharged after 15 days with clinical improvements.